The co-teaching book of lists - Perez, Katherine D. (San Francisco, CA Jossey-Bass, 2012)
"Practical strategies for teachers who share classroom teaching responsibilitiesFilled with down-to-earth ideas, suggestions, strategies, and techniques, The Co-Teaching Book of Lists provides educators with a hands-on resource for making the co-teaching experience a success. Written by educator and popular teacher trainer Kathy Perez, this book gives educators a classroom-tested and user-friendly reference for the co-taught classroom. Topics covered include: roles and responsibilities; setting up the classroom; establishing classroom climate; effective accommodations and modifications for students; goal-setting; negotiating conflicts; scheduling issues; and more. Author Katherine Perez is a popular presenter and workshop leader for Bureau of Education and Research and Staff Development for Educators Offers best practices and helpful strategies for making co-teaching a success Includes a wealth of ideas that are both practical and easy to implement This easily accessible reference presents numerous positive and ready-to-use tips, strategies, and resources for collaborative teaching and student success"--Provided by publisher.
Machine generated contents note: About the Author Acknowledgments Foreword by Harry Wong Preface Introduction Chapter 1: Co-Teaching in a Nutshell 1.1 Characteristics of Co-Teaching 1.2 What Co-Teaching Is 1.3 What Co-Teaching Is Not 1.4 Framework for Co-Teaching 1.5 How Co-Teaching Benefits Teachers 1.6 Advantages for the General Education Teacher 1.7 Advantages for the Special Education Teacher 1.8 Advantages of Co-Teaching for Students 1.9 Advantages for the General Education Student 1.10 Advantages for the Special Education Student 1.11 Considerations for Starting a New Co-Teaching Initiative 1.12 Where Does Co-Teaching Take Place? 1.13 Terms Co-Teachers Need to Know 1.14 Opening Assumptions for Co-Teaching 1.15 A Co-Teaching Anticipation Guide 1.16 The Beginning Stages of Co-Teaching Chapter 2: Co-Teaching Models Level 1: Large-Group Instruction 2.1 One Teach, One Observe 2.2 One Teach, One Drift 2.3 One Teach, One Assist or Support 2.4 Team Teaching Level 2: Small-Group Instruction 2.5 Station Teaching 2.6 Parallel Teaching 2.7 Alternative Teaching Variations of Models 2.8 Skill Group Teaching 2.9 Speak and Add Model 2.10 Duet Teaching 2.11 Adapting Curriculum Approach 2.12 Learning Styles Approach 2.13 Checking In: Applying the Approaches 2.14 Co-Teaching Approaches: An Action Plan 2.15 Applying the Models: Develop and Do Chapter 3: Where Do You Start? 3.1 First Steps for Beginning the Co-Teaching Experience 3.2 Second Steps 3.3 Preparing for Co-Teaching: A Checklist to review 3.4 Preparing to Teach Together 3.5 Co-Teaching Planning Pointers 3.6 Ongoing Implementation 3.7 Co-Planning Tips and Tricks 3.8 Maximizing Lesson Planning Time 3.9 Co-Teaching Weekly Planning Guide 3.10 Practical Planning Pointers 3.11 Planning a Co-Taught Unit 3.12 Co-Teaching Planning Form 3.13 Reviewing the Co-Planning Process 3.14 Co-Teaching Roles and Responsibilities 3.15 Determining Roles and Responsibilities 3.16 Role Clarity 3.17 Sample Co-Teaching Duties 3.18 Introducing the Co-Teaching Team 3.19 Who Does What in a Co-Taught Classroom? 3.20 A Framework for Co-Teaching 3.21 Communication Issues and Co-Teaching 3.22 Conversation Starters" 3.23 Communication Tips and Techniques 3.24 Collaboration Is the Key 3.25 Ways to Ease in a Special Educator as a Partner in the Classroom 3.26 A Blueprint for Collaborative Teaching Chapter 4: Where Do You Go? A Co-Teaching Roadmap 4.1 Scheduling Considerations for Co-Teaching 4.2 Effective Methods for Placing Students in a Co-Taught Classroom 4.3 Finding Time to Plan 4.4 Co-Teaching Daily Lesson Plans 4.5 Expanding Planning Time for Co-Teaching 4.6 Using Planning Time Effectively 4.7 Application: Putting Planning into Action 4.8 Co-Planning Agenda Tips 4.9 Procedures and Routines 4.10 Scheduling Co-Teaching Chapter 5: Collaboration: Working as a Team 5.1 What Is a Team? 5.2 Characteristics of Co-Teaching Teams 5.3 Forming an Effective Co-Teaching Team 5.4 Ingredients of Excellence for Your Co-Teaching Teams 5.5 Relationship Building Blocks 5.6 Team Preparation: What Do I Bring? 5.7 Team-Building Personality Preferences 5.8 Personality Style Activity 5.9 Co-Teaching Conversations 5.10 Co-Teaching Decision Making 5.11 Potential Challenges 5.12 Overcoming Roadblocks: Solutions 5.13 Dealing with Conflict 5.14 Steps to Take 5.15 Communication and Accountability Tools 5.16 Checking In: How Is Our Co-Teaching Going? 5.17 Collaborative Problem-Solving Worksheet Chapter 6: Organizing and Planning for Success 6.1 Celebrating All Learners: Strategies for Success 6.2 Helpful Online Resources 6.3 Physical Organization 6.4 Strategies for Flexible Grouping 6.5 Small-Group Strategies 6.6 Working Together for Small-Group Success 6.7 Advantages of Small-Group Instruction 6.8 Small-Group Planning 6.9 Points to Ponder: Large-Group Instruction 6.10 Planning for Large-Group Instruction 6.11 Independent Student Work 6.12 Goal Setting: Keeping Score 6.13 Choices, Not Chance, in Your Curriculum 6.14 Procedures and Routines 6.15 Co-Teaching Conversations 6.16 Routines That Are Important for Co-Teachers to Share 6.17 Looking at Your Classroom from a Student's Perspective 6.18 Additional Procedure Pointers 6.19 Supporting Student Behavior 6.20 Classroom Rules That Work 6.21 Behavior Intervention Worksheet 6.22 Student Survey 6.23 How Are You Smart? Multiple Intelligences Survey Chapter 7: Schoolwide Organization: Administrative Issues 7.1 Schoolwide Issues 7.2 Barriers to Successful Co-Teaching 7.3 Professional Development Issues 7.4 Scheduling Issues 7.5 Effective Methods for Placing Students 7.6 Techniques for Classroom Caseloads 7.7 Guiding Principles 7.8 Student Study Teams--a Pre-Referral Strategy 7.9 Student Study Team Guidelines 7.10 Roles and Responsibilities of Team Members 7.11 How Administrators Can Support Co-Teaching 7.12 Other Ways Administrators Can Support the Co-Teaching Team 7.13 Observing Co-Teachers 7.14 Providing Feedback 7.15 Co-Teaching Observation Form Chapter 8: Accommodations and Modifications That Make a Difference 8.1 What Are Accommodations, Modifications, and Interventions? 8.2 Modification Versus Differential Standard 8.3 Accommodations and Modifications Log 8.4 Accommodations or Modifications? 8.5 Adapting Instruction Flow Chart 8.6 Planning Guide to Curriculum Modifications 8.7 Modifications On the Move 8.8 Co-Teacher Communication Cards 8.9 Checklist of Accommodations and Modifications 8.10 Focus on Curriculum Adaptations 8.11 Adaptation Application Activity 8.12 Strategies for Supporting Students with Special Needs in the General Education Classroom 8.13 A Closer Look at Special Needs Challenges and Choices for Co-Teaching 8.14 I Have a Student Who...What to Do? 8.15 Modifications Based on Students' Learning Styles 8.16 Adaptations and Modifications Chart 8.17 Class List: Adaptation Chart and Learning Profile 8.18 Evaluation Process in a Co-Taught Classroom 8.19 Accommodations for Testing in a Co-Taught Classroom 8.20 Revising Grading Procedures Chapter 9: Instructional Strategies for Different Types of Learners 9.1 Getting Started with Strategies That Make a Difference 9.2 Engaging Strategies for Co-Teaching 9.3 Your Multiple Intelligences Toolkit 9.4 Product Possibilities 9.5 Think-Tac-Toe Choice Menus of Activities 9.6 Think-Tac-Toe Activity Board 9.7 Vocabulary Bingo 9.8 Book Report Activity Board 9.9 Cubing 9.10 Cubing in the Content Areas 9.11 "Let 'em Roll": Cubing Task Cards 9.12 Bloom's Building Blocks 9.13 Cubing Pattern 9.14 Cubing Companion Activity Sheet 9.15 Bloom's Taxonomy 9.16 Graphic Organizers 9.17 Why Use Graphic Organizers? 9.18 How Do You Use Graphic Organizers? 9.19 Herringbone Graphic Organizer 9.20 Double-Entry Journal 9.21 Learning Centers 9.22 Centers Planning Guide 9.23 Keeping Students on Target 9.24 Learning Contract 9.25 Anchor Activities 9.26 Activating Strategies 9.27 Techniques to Set the Stage for Learning 9.28 Strategies to Support Learning During Instruction 9.29 A Closer Look: During-Instruction Strategies 9.30 After-Reading Strategies 9.31 Summarizer Activities to Reflect on Learning 9.32 Culminating Review Games Chapter 10: Reflecting on Practice and Planning: Tools for Moving Ahead 10.1 Maintaining an Effective Co-Teaching Partnership 10.2 Taking It One Step at a Time 10.3 Co-Instruction: Where Are You Now? 10.4 The Co-Teaching Rating Scale 10.5 Co-Teaching Road Map 10.6 Looking Ahead: Planning Guide 10.7 Student Profile 10.8 Making the Most of Lesson-Planning Time 10.9 Co-Planning Agenda Framework 10.10 Lesson Preparation Pointers 10.11 Co-Teaching Lesson Planning Worksheet 10.12 Co-Teaching Lesson Planning Template 10.13 Keeping Track Appendix: Questions for Discussion Notes Additional Resources Index.
Includes bibliographical references and index.
"Grades K-12."
Keywords: Teaching teams